1983
DOI: 10.1152/jn.1983.49.2.424
|View full text |Cite
|
Sign up to set email alerts
|

A further examination of effects of cortical stimulation on primate spinothalamic tract cells

Abstract: 1. Stimulation of the sensorimotor cortex was found to excite and/or inhibit nociceptive spinothalamic tract cells. Thirteen wide dynamic range cells were inhibited by cortical stimulation, 6 were excited and 14 were both excited and inhibited. Four of six high-threshold cells were excited and one was inhibited. 2. Intermediate (200 ms) or long (2 s) duration conditioning trains were effective in reducing responses of spinothalamic cells evoked by noxious mechanical or thermal stimuli and by A- and C-fiber vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
1

Year Published

1985
1985
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 0 publications
4
42
0
1
Order By: Relevance
“…Concurrent reductions in pulse and respiration in this study indicate that relaxation or distraction reduces sympathetic activity as they reduce pain. In addition, music is known to stimulate the sensory cortex and the thalamus which have been found to inhibit nociceptive neurons in the spinal cord (Vidal and Jacob, 1980;Andy, 1983;Dickenson, 1983;Yezierski et al, 1983), and has been found to increase immune factors (Lane and Olness, 1991). Sears and Carroll (1998) have questioned the clinical significance of small differences between relaxation and control groups in pain studies.…”
Section: Support Of Theorymentioning
confidence: 99%
“…Concurrent reductions in pulse and respiration in this study indicate that relaxation or distraction reduces sympathetic activity as they reduce pain. In addition, music is known to stimulate the sensory cortex and the thalamus which have been found to inhibit nociceptive neurons in the spinal cord (Vidal and Jacob, 1980;Andy, 1983;Dickenson, 1983;Yezierski et al, 1983), and has been found to increase immune factors (Lane and Olness, 1991). Sears and Carroll (1998) have questioned the clinical significance of small differences between relaxation and control groups in pain studies.…”
Section: Support Of Theorymentioning
confidence: 99%
“…Reduced muscular and mental tension also decrease sympathetic stimulation of the hypothalamus (Beary & Benson, 1974). These processes inhibit transmission of afferent noxious impulses in the central nervous system by activating endogenous opiates, descending nerve impulses, and neuropeptides in the brain and spinal cord (Andy, 1983;Yezierski, Gerhart, Schrock, & Willis, 1983). Recent imaging studies showed that distraction decreased reported sensory pain and also modulated activity in the sensory cortex, while verbal suggestions decreased reported affective pain and also modulated activity in the anterior cingular cortex (Rainville, Carrier, Hofbauer, Bushnell, & Duncan, 1999).…”
mentioning
confidence: 99%
“…The clinical data we reported 27 , however, strongly suggest that if VB stimulation really inhibits DH nociceptive neurons, this mechanism should play at most a partial and not the most important role in the pain relief accomplished by this procedure. 30 suggested that the inhibitory effects of SI stimulation on the DH nociceptive neurons could be mediated by both corticospinal and extrapiramidal tracts. Based on these findings, Gerhart et al 11 proposed that VB stimulation produces pain relief by activation of these corticofugal pathways.…”
Section: Vb Stimulation Produces Pain Relief By Antidromic Activationmentioning
confidence: 99%
“…There is also experimental evidence against this hypothesis: A) Aiko et al 2 demonstrated increase in local glucose utilization in SI, but not in the DH, following VB stimulation, B) SI stimulation inhibits preferentially DH nociceptive neurons responses to innocuous stimuli while VB stimulation has no preferential effect, although DH nociceptive cells responses to C fiber volleys are reduced to a greater extent than their responses to A fiber volleys 11,30 , C) SI stimulation ipsilateral to an spinothalamic tract neuron produces only weak inhibitory effects, while ipsilateral VB stimulation usually causes a powerful inhibition 11 and D) Inhibition of the responses of spinothalamic cells to noxious stimuli following VB stimulation is observed even when SI stimulation fails to inhibit the responses of the same cells to such stimuli 11 .…”
Section: Vb Stimulation Produces Pain Relief By Antidromic Activationmentioning
confidence: 99%
See 1 more Smart Citation